Ta’ṡiru Uslūbi al Tadrīsi al Tabādulī alā Mahārati al Qirā’ati fī Ta’līmi al Lughati al ‘Arabiyyati - Hardiyanti, Putri; Hakim, Faridl (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
The purpose of this research is to find out the effect of reciprocal teaching style on reading skill in teaching Arabic in the first grade of secondary school in Dar Al-Muwahhidin Islamic Institute Panyalaian Tanah Datar. The author uses an experimental research methodology with three data machines, which means observation guide, interview guide, and exam questions. . To find out these issues, the author used field research using the experimental method. The research design is Tru Eksperimental Design, of the type The Post-test only Control Group Design. After the writer uses the reciprocal teaching method, she finds that the maximum reading skill score is 93 and the lowest score is 70. Then the author finds that the result of t_(0) is greater than the Therefore, the hypothesis of nihilism is reversible and the hypothesis of reciprocity is acceptable, and it is intended to find the difference between the result of the reading skill using the reciprocal teaching method and without using the reciprocal teaching method. The conclusion from this research is that the method of reciprocal teaching affects the outcome of reading skill. Therefore, the Arabic language school, especially in the skill of reading, must use the method of reciprocal teaching in teaching the skill of reading so that students understand reading well. result of t_(t), which is 01,3>3,52>16,2.